Macrohematuria as the leading symptom in geriatric urology patients - Küper, L.; Wiedemann, A.; Heppner, Hans Jürgen (Urologe, 2019)
BACKGROUND: Macrohematuria is a frequent reason for hospitalization of elderly urologic patients. Anticoagulants and long-term catheterization often play a role and are characterized in the current paper. METHODS: In all, 162 patients hospitalized due to macrohematuria and older than 75 years were retrospectively observed concerning demographic data, clinical risk factors, potential reasons for macrohematuria and the necessary interventions. RESULTS: The observed patients were on average 84.74 years old and had a medium score of 2.72 in the geriatric screening as "with geriatric need of action". A total of 65.4% had a Foley or suprapubic catheter. Initial measures included continuous bladder irrigation in 42.6% and catheter replacement in 39.5%. The amount of blood loss was 1.27 mg/dl hemoglobin. There was no significant difference in bacterial bladder infection in patients with or without a catheter (51.7 vs. 42.6%, p = 0.51). In all, 75.3% of the patients were under anticoagulation therapy; of these, 40.6% were undertreated with vitamin K antagonists, 28.1% overtreated and 31.2% were in the target range. Urologic workup diagnosed 25.3% of patients with tumors of the urinary bladder, the prostate or ureter. CONCLUSION: A bladder catheter is a risk factor for more intensive macrohematuria. Contrary to expectations, overdosage was not the leading reason for hematuria for patients taking vitamin K antagonists. Even for elderly, geriatric patients under anticoagulation, the urologic diagnostic workup demonstrated a high percentage of significant malignancies. Diagnostic procedures should not be neglected even for these patients.
EVALuna2:52981